THE COMPARISON OF USING CHAIN WORD AND PICTIONARY GAMES TOWARD VOCABULARY MASTERY - Syaifudin Latif Darmawan; Grassilia Nenny Fatmawati (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
Vocabulary is a main component in learning English. In instructional process, the teachers often apply some kinds of method, technique, and media of vocabulary mastery in teaching and learning process which can make the students bored, lazy, inactive and annoyed to remember the main part of English. This research is proposed to know the distinction between student’s vocabulary mastery instructed by using chain word and Pictionary games at eighth grade students of SMP N 1 Pekalongan and to prove which one of the game is more effective than others. The design of this research is Non-Equivalent Control Group Design. The research is conducted at eighth grade of SMPN 1 Pekalongan. The researcher employs stratified cluster random sampling to take the sample. The population is 576 students in 19 classes and the eighth grade is the sample of this research, 8.1 is as the experimental class and 8.4 is the control class. Based on the result of research, there is a significant distinction of the result between pre-test and post-test score in experimental and control class. The scores indicated that Pictionary game is more effective than chain word game toward students’ vocavulary at eighth grade of SMPN 1 Pekalongan.